Mengasah Kecakapan Berwirausaha : Strategi dan Keterampilan yang Diperlukan untuk Sukses - Agustinus Tandi la’bi’; Lisa Sababalat (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This article discusses the importance of honing entrepreneurial skills as the main key to achieving success in an increasingly competitive business world. Entrepreneurial skills include various aspects involving technical and non-technical skills that can support business development, such as creativity, time management, leadership, and decision-making skills. This article also identifies several strategies that aspiring entrepreneurs need to implement to increase their chances of success, including careful business planning, the ability to adapt to market changes, and the use of technology and innovation. Apart from that, the importance of interpersonal skills and a wide network in building business relationships was also discussed. By mastering the right skills and implementing effective strategies, it is hoped that entrepreneurs can overcome challenges and achieve sustainable success in the business world.